THE EVALUATION OF MICROBIOLOGICAL, PHYSICOCHEMICAL, AND SENSORY PROPERTIES OF RICE BRAN YOGURT WITH CAVENDISH BANANA (MUSA ACUMINATA) PUREE ADDITION AT VARIOUS CONCENTRATIONS - Ira Nugerahani; Florencia Irena Cahyadi; Philomena Caroline Hartono; Indah Kuswardani; Susana Ristiarini; Ignatius Srianta; Ihab Tewfik (Soegijapranata Catholic University, 2024)
Cavendish banana is a widely known fruit for its high saccharide content and many volatile aroma compounds (esters and alcohols). Integrating Cavendish banana into rice bran yogurt [RBY] is expected to enhance its sensory properties. However, its contents of starch, simple sugars, and organic acids may affect LAB's growth, which impacts the physicochemical and sensory properties of RBY. The aim of this study was to ascertain the microbiological, physicochemical, and sensory properties of RBY integrated with Cavendish banana puree [CBP] at various concentrations. Experimental yogurts were made from full cream UHT milk supplemented with 1% rice bran and different levels of CBP (0%, 5%, 10%, 15%, 20%, and 25% (w/v)) and then inoculated with a yogurt starter. Results showed that the integration of CBP has significantly (P 0.05) affected the LAB counts, pH, and sensory preferences of RBY (appearance and mouthfeel). However, it has no significant (P 0.05) effect on the titratable acidity (as %lactic acid), syneresis, and taste preference of RBY. Increment levels of CBP integration reduced the appearance and mouthfeel preferences, while taste preference tended to increase up to 15% level of integration. CBP exerted a praising effect on the microbiological, physicochemical, and sensory properties of RBY.